Implementation of Risk Management Strategies in the Industrial Sector - Suwanda, Suwanda (Jurnal Sosial Sains dan Komunikasi, 2024)
Risk management is a crucial aspect in a dynamic business environment, especially in industries related to various risks such as financial, operational and environmental. This research will identify risk management strategies commonly used in industrial contexts and analyze the extent to which their implementation minimizes the impact of possible risks. This research uses a qualitative approach with descriptive methods. The research results show that implementing an effective risk management strategy has a positive impact on the company's development in the long term. Companies that succeed in minimizing the risks associated with developing new products and acquiring funds are more likely to be able to survive in the market and achieve significant growth. A good risk management system helps companies plan smart and efficient business steps, strengthen their position in the market, and increase the potential for long-term success. Implementing appropriate risk management strategies is also key to reducing the impact of possible risks, enabling growth into a successful company in a dynamic market. Steps such as planning, risk identification, risk evaluation and risk mitigation are essential in achieving sustainable business success